2003
DOI: 10.5194/acpd-3-769-2003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of volatile organic compounds in the polluted urban atmosphere of Bristol, UK

Abstract: Abstract. The results of a field campaign carried out from early spring through to the late summer of 2000, in Bristol, England, are presented. Continuous measurements of over 40 hydrocarbons have been made at an urban background site, located at Bristol University, for approximately nine months using a GC-FID system and for a selection of halocarbons for approximately one month using a GC-ECD system. In this paper we present the time-series of the nine halocarbons and selected hydrocarbons. Daytime and night-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The alkenes chosen were a compromise between availability of data for analysis and reactivity of the alkenes. Rivett et al (2003) have shown that the method works best when the most reactive alkenes are chosen; however, in order to have consistency throughout the time period examined, we were mindful of choosing a set [OH] and k disp by using the alkane decay alone, three calculations were made using n-butane and n-pentane, n-butane and n-hexane, n-butane and n-heptane, respectively. As the reactivity of alkanes follows the order n-heptane > nhexane > n-pentane > n-butane, the estimation was more accurate for n-heptane than for the corresponding smaller alkanes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The alkenes chosen were a compromise between availability of data for analysis and reactivity of the alkenes. Rivett et al (2003) have shown that the method works best when the most reactive alkenes are chosen; however, in order to have consistency throughout the time period examined, we were mindful of choosing a set [OH] and k disp by using the alkane decay alone, three calculations were made using n-butane and n-pentane, n-butane and n-hexane, n-butane and n-heptane, respectively. As the reactivity of alkanes follows the order n-heptane > nhexane > n-pentane > n-butane, the estimation was more accurate for n-heptane than for the corresponding smaller alkanes.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrocarbon decay method developed by Rivett et al (2003) has been used to analyse urban hydrocarbon data from four contrasting sites in the United Kingdom. Remarkably consistent results emerge from the analysis using alkenes, revealing NO 3 levels in the range 0.01-10 ppt and OH levels in the range 1 × 10 4 -1 × 10 6 molecule cm −3 , with an average of about 2 × 10 5 molecule cm −3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In past years, the exposure levels of commuters to volatile organic compounds (VOCs) inside public transport modes have been reported in several urban locations in Europe, Asia and megacities such as Mexico City [1]- [4]. These studies have raised interest and serious concern about the impact of organic compounds emitted by automotive traffic on human health and air quality, which is now recognized as a major environmental problem in urban areas [5]- [7]. The available information indicates that commuting can cause elevated personal exposure to toxic VOCs, including compounds known as carcinogenic such as benzene, which is closely linked to the induction of leukemia [8] [9].…”
Section: Introductionmentioning
confidence: 99%